In-depth appreciation of social inequalities in Charles Dickens’s Oliver twist - Olivier, ABODOHOUI Orerien; Telesphore, DIKPO Toliton (Edelweiss Applied Science and Technology, 2024)
This study intends to appreciate the issues of social inequalities that the world is facing as disclosed in Charles Dickens’s Oliver twist in the Victorian period. Understanding the historical, social, political and economic contexts in the Victorian Period that paved a way to social inequalities in England is crucial for an in-depth appreciation of the matter. In exploring social realism in Dickens’s Oliver Twist (1837), it becomes obvious that the novel serves as a powerful lens into the harsh realities of Victorian London’s social inequalities that the author experienced during his lifetime as British author during the industrial revolution. The stark contrast between the wealthy and the poor, the harsh conditions faced by the working class, and the social injustices prevalent in 19th-century influenced Dickens’s portrayal of society in the novel under study through the story of an orphan boy named Oliver Twist. The main purpose of this study is to appreciate how social inequalities are demonstrated in England, particularly through Charles Dickens’s Oliver twist and its impacts or effects on the society and individual. To achieve my goals, I have used qualitative research with Charles Dickens’s Oliver twist as primary source. Moreover, Marxism, structuralism and New Historicism have been used as appropriate theories. My research reveals that Charles Dickens has used his fictional world to shed light on many social inequalities such as poverty, social stratification and child labor. It illustrates that inequality is source of many offences. Social inequalities appear as an actual fact that makes the balance between the social environment and one living conditions. Thus, this article ends up giving some alternatives on how to reduce social inequalities.